Cation–anion interaction directed dual-mode switchable mechanochromic luminescence. Issue 33 (10th August 2017) - Li, Gaocan; Xu, Yangyang; Kong, Qunshou; Zhuang, Weihua; Wang, Yunbing
Abstract : Dual-mode switchable mechanochromic luminescence triggered by tunable cation–anion interactions has been reported based on a single tributyl(perylen-3-ylmethyl)phosphonium (TPMP ) fluorophore. Abstract : In the past few years, organic mechanochromic materials have attracted more and more attention and a number of organic mechanochromic materials have been reported. However, only a single mode for switching of mechanochromic luminescence, either red-shift or blue-shift of the luminescence, can be observed for all the reported mechanochromic materials. Herein, based on a single tributyl(perylen-3-ylmethyl)phosphonium (TPMP ) fluorophore, dramatic dual-mode switchable mechanochromic luminescence triggered by tunable cation–anion interactions has been reported for the first time. The trend of mechanochromic luminescence changes gradually from a red-shift to a blue-shift along with the strength order of the cation–anion interaction: Br − > BF4 − > PF6 − > NTf2 − . A reversible transition of a crystalline state to an amorphous phase might be involved in the mechanochromic luminescence ofTPMP·X (X = counteranion) with different counteranions.